Canadian Public Health Laboratory Network laboratory Guidelines for the Diagnosis of Neurosyphilis in Canada - Tom Wong; Kevin Fonseca; Max A Chernesky; Richard Garceau; Paul N Levett; Bouchra Serhir (Canadian Journal of Infectious Diseases and Medical Microbiology)
Neurosyphilis refers to infection of the central nervous system by Treponema pallidum, which may occur at any stage. Neurosyphilis has been categorized in many ways including early and late, asymptomatic versus symptomatic and infectious versus non-infectious. Late neurosyphilis primarily affects the central nervous system parenchyma, and occurs beyond early latent syphilis, years to decades after the initial infection. Associated clinical syndromes include general paresis, tabes dorsalis, vision loss, hearing loss and psychiatric manifestations. Unique algorithms are recommended for HIV-infected and HIV-uninfected patients, as immunocompromised patients may present with serologic and cerebrospinal fluid findings that are different from immunocompetent hosts. Antibody assays include a VDRL assay and the FTA-Abs, while polymerase chain reaction for T. pallidum can be used as direct detection assays for some specimens. This chapter reviews guidelines for specimen types and sample collection, and identifies two possible algorithms for use with immunocompromised and immunocompetent hosts using currently available tests in Canada, along with a review of treatment response and laboratory testing follow-up.